Oligonychus karamatus (Ehara) new to Slovenia (Acari: Tetranychidae) - Vierbergen, Gijsbertus (Acta entomologica slovenica (Ljubljana), 2003)
Oligonychus karamatus (Ehara) was found in the Julian Alps infesting Larix decidua Miller. This is the first record of this Palaearctic spider mite in Slovenia and the most western in its distribution area.
Keywords: Acari; entomologija; pršice; Slovenia; Slovenija